2018
DOI: 10.1016/j.nicl.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating structural and perfusion deficits due to repeated head trauma in active professional fighters

Abstract: Repeated head trauma experienced by active professional fighters results in various structural, functional and perfusion damage. However, whether there are common regions of structural and perfusion damage due to fighting and whether these structural and perfusion differences are associated with neuropsychological measurements in active professional fighters is still unknown. To that end, T1-weighted and pseudocontinuous arterial spin labeling MRI on a group of healthy controls and active professional fighters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
(109 reference statements)
2
7
0
Order By: Relevance
“…Depending on the severity and the type of injury, RHI has been shown to produce a cascade of both regional and global brain atrophy (Bigler, 2013;Eierud et al, 2014;Gooijers et al, 2013;Koerte et al, 2015;Langlois et al, 2006). However, similar to our previous findings (Mishra et al, 2018), in our cohort of active professional fighters, we did not find any global or regional VBM differences between our current cohort of impaired and nonimpaired boxers. We speculate that regional or global atrophy due to RHI may lack both sensitivity and specificity for a significant group effect earlier in the pathological process, possibly due to the heterogeneous impact of brain injuries and the inherent repair mechanism of individual boxers.…”
Section: Vbm and Its Role In Rhisupporting
confidence: 82%
“…Depending on the severity and the type of injury, RHI has been shown to produce a cascade of both regional and global brain atrophy (Bigler, 2013;Eierud et al, 2014;Gooijers et al, 2013;Koerte et al, 2015;Langlois et al, 2006). However, similar to our previous findings (Mishra et al, 2018), in our cohort of active professional fighters, we did not find any global or regional VBM differences between our current cohort of impaired and nonimpaired boxers. We speculate that regional or global atrophy due to RHI may lack both sensitivity and specificity for a significant group effect earlier in the pathological process, possibly due to the heterogeneous impact of brain injuries and the inherent repair mechanism of individual boxers.…”
Section: Vbm and Its Role In Rhisupporting
confidence: 82%
“…Magnetic resonance imaging (MRI) can be used to investigate changes in regional brain volumes, perfusion, structural connectivity [derived using diffusion‐weighted MRI (dMRI)], and functional connectivity in participants exposed to RHI. For instance, various structural neuroimaging studies of RHI due to combat sports and in veterans with blast injuries have shown changes in various gray matter volumes such as thalamus, ventromedial prefrontal cortices, right fusiform gyrus, and frontotemporolimbic regions involving hippocampus, medial temporal lobe, and frontal lobes (Bernick et al, ; Bigler, ; Gooijers et al, ; Lopez‐Larson et al, ; Mishra et al, , ; Montenigro, Bernick, & Cantu, ; Ng et al, ). Similarly, voxelwise dMRI‐derived measures such as fractional anisotropy (FA) and mean diffusivity (MD) have shown differences in the temporo‐occipital white matter tracts and forceps major (Hulkower, Poliak, Rosenbaum, Zimmerman, & Lipton, ; Mishra et al, ; Ng et al, ; Orrison et al, ; Shin et al, ; Wintermark, Sanelli, Anzai, Tsiouris, & Whitlow, ; Zhang et al, ; Zhang, Heier, Zimmerman, Jordan, & Ulug, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, voxelwise dMRI‐derived measures such as fractional anisotropy (FA) and mean diffusivity (MD) have shown differences in the temporo‐occipital white matter tracts and forceps major (Hulkower, Poliak, Rosenbaum, Zimmerman, & Lipton, ; Mishra et al, ; Ng et al, ; Orrison et al, ; Shin et al, ; Wintermark, Sanelli, Anzai, Tsiouris, & Whitlow, ; Zhang et al, ; Zhang, Heier, Zimmerman, Jordan, & Ulug, ). Finally, perfusion measures using arterial spin labeling (ASL) MRI has also shown significant deficits in the thalamus, cingulate gyri, cerebellum, cuneus, and temporal lobes (Eierud et al, ; Koerte et al, ; Mishra et al, ). Even multivariate MRI measures combining voxelwise volumetric, perfusion, and dMRI‐derived measures (Mishra et al, , ) have identified deficits in several brain regions that were correlated with exposure and neuropsychological scores in participants with RHI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, the evaluation of whole hippocampal volume was not a well-suited biomarker during the pre-clinical AD stage. Several papers reported contradictory findings, potentially due to the use of different approaches in performing the analyses [ 123 ]. This could be related to the fact that the manual volumetric technique is a very challenging and time-consuming approach also requiring an excellent working knowledge of neuroanatomy as well as good skill in delineating regions of interest (ROI).…”
Section: Emerging Ad “Dry” Biomarkers: Structural and Functional Tmentioning
confidence: 99%